The current state of the dance sport movement at secondary school clubs in Hai Ba Trung district, Hanoi (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
The current state of the dance sport movement at secondary school clubs in Hai Ba Trung district, Hanoi